OCB Makeover: Turning Passive Presence into Proactive Contribution - Pitensah, Chintia Noviela; Sahrah, Alimatus (Universitas Mercu Buana Jakarta, 2025)
Organizational Citizenship Behavior (OCB) is a critical component in fostering teamwork, building a positive organizational climate, and driving collective performance. Yet, many employees, especially those in operational roles, demonstrate low to moderate levels of OCB, which can hinder organizational effectiveness. While previous research has largely explored personality traits or leadership influences on OCB, limited studies have tested structured interventions designed to enhance OCB by developing proactive behavior in employees. This study addresses this gap by implementing a proactive personality training program and evaluating its impact on OCB among employees in a production unit. Using a quasi-experimental design, the training was delivered to a group of employees identified with low to moderate OCB levels, while a comparable group served as a control. OCB was assessed before and after the intervention using a validated measurement tool. The results showed clear improvements in OCB following the training, with trained employees demonstrating more cooperative, helpful, and initiative-driven behaviors in the workplace. These findings suggest that proactive personality traits can be cultivated through training and have meaningful effects on organizational functioning. This study offers a practical and scalable strategy to promote prosocial workplace behavior and contributes a novel perspective to intervention-based OCB research.